2019
DOI: 10.1186/s40900-019-0170-2
|View full text |Cite
|
Sign up to set email alerts
|

PPI in research: a reflection from early stage researchers

Abstract: Background: The importance of patient and public involvement (PPI) in the design and conduct of health research projects is gaining widespread recognition; however, it is still a developing area. Furthermore, PPI in methodological health research can help increase research value Thus, it is of great importance that researchers, especially early stage researchers continue to discuss and learn about the future challenges and opportunities of PPI. Objective: With this commentary, we aim to disseminate i) key mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
(40 reference statements)
0
27
0
Order By: Relevance
“…This may encourage a wider range of individuals to get involved in PPI activities. However, some researchers may not see the value and feasibility of PPI [ 22 , 23 ]. Furthermore, researchers may be disinclined to try a novel approach if they feel daunted by the prospect of embedding PPI into their work, especially when resources to undertake this activity in a meaningful manner are lacking [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may encourage a wider range of individuals to get involved in PPI activities. However, some researchers may not see the value and feasibility of PPI [ 22 , 23 ]. Furthermore, researchers may be disinclined to try a novel approach if they feel daunted by the prospect of embedding PPI into their work, especially when resources to undertake this activity in a meaningful manner are lacking [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may encourage a wider range of individuals to get involved in PPI activities. However, there may still be the challenge of researchers seeing the value and feasibility of PPI [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…We recruited young people through broad local advertisements and invitations via schoolteachers to students (at secondary school or college) to be part of the project. Two young amateur artists (E. Prior aged 17 and M.Viljoen aged 19) responded and worked with the team on this project. MV attended workshops in Bristol and Keele, whilst EP was at the Oxford workshop.…”
Section: Artists and Art Involvementmentioning
confidence: 99%
“…The involvement of 'consumers and the community' or 'patients and the public' is increasingly recognised as important in healthcare decision making [14], as well as design and conduct of research [15][16][17] and setting of research priorities [18]. Consumer and community involvement ensures that research focuses on issues relevant to the public [19] and has been shown to have an impact at all stages of research [20].…”
Section: Consumer and Community Involvement In Health Researchmentioning
confidence: 99%